Development of science LKPD based on inquiry training on HOTS-science literacy skills - Dini Rozali; Retno Dwi Suyanti; Rosmala Dewi (Inovasi Kurikulum, 2024)
LKPD circulating in schools mostly does not contain experiments, demonstrations or discussions. This research aims to produce worksheets for students as teaching materials used in the science learning process, thereby creating maximal learning activities that provide space for students to be active in thinking through inquiry-based learning activities, thus improving students' HOTS-Science Literacy. This study is development research using the ADDIE development model (analysis, design, development, implementation, and evaluation), with the research subjects being fifth-grade students of SDN 060874 Medan. The research instruments used were validation questionnaires for expert validators and student response questionnaires regarding the practicality of the resulting product. The results obtained from the research show that the Inquiry Training-Based Science Worksheet is in the highly valid category, with percentages for three consecutive worksheets being 96 percent, 98 percent, and 97 percent based on the assessment from expert validators. The practicality test was analyzed based on student responses, with an average score of 78.7 percent, which falls into the practical category. Based on the results of the data analysis, it was concluded that the Science LKPD based on Inquiry Training was valid and practical to be used as alternative teaching material for teachers to improve the ability of HOTS-science literacy of grade V elementary school students.   Abstrak LKPD yang beredar di sekolah kebanyakan tidak memuat kegiatan eksperimen, demonstrasi maupun diskusi. Penelitian ini bertujuan untuk menghasilkan lembar kerja untuk peserta didik sebagai bahan ajar yang digunakan di dalam proses pembelajaran IPA sehingga terciptanya aktivitas belajar yang maksimal dalam memberi ruang kepada peserta didik untuk aktif dalam berpikir melalui kegiatan pembelajaran berbasis inquiry training sehingga meningkatkan kemampuan HOTS-Literasi Sains peserta didik. Penelitian ini merupakan penelitian pengembangan dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation) dengan subjek penelitiannya adalah peserta didik kelas V SDN 060874 Medan. Instrumen penelitian menggunakan lembar angket validasi untuk ahli validator dan angket respons peserta didik terhadap kepraktisan produk yang dihasilkan. Adapun hasil penelitian yang diperoleh menunjukkan LKPD IPA Berbasis Inquiry Training berada pada kategori sangat valid dengan persentase kepada tiga LKPD berturut-turut 96 persen, 98 persen, dan 97 persen berdasarkan penilaian dari ahli validator. Uji kepraktisan dianalisis berdasarkan respons peserta didik dengan perolehan rata-rata skor sebesar 78,7 persen yang berada pada kategori praktis. Berdasarkan hasil analisis data tersebut disimpulkan bahwa LKPD IPA berbasis Inquiry Training telah valid dan praktis untuk digunakan sebagai bahan ajar alternatif bagi guru dalam upaya meningkatkan kemampuan HOTS-literasi sains peserta didik kelas V SD. Kata Kunci: HOTS-literasi sains; inquiry training; IPA; LKPD